Analysis of Mathematical Communication Ability and Curiosity Through Project Based Learning Models With Scaffolding - Paruntu, Patrice Ester; Sukestiyarno, YL.; Budi Prasetyo, Andreas Priyono (Universitas Negeri Semarang, 2018)
This study aims to: (1) test the effectiveness of project based learning model with scaffolding in improving mathematical communication skills, and (2) to describe mathematical communication skills and students' curiosity through the project based learning model with scaffolding. This research uses approach of mix method of sequential explanatory type. The subject of the research are the students of VIIA class of State Junior High School 18 North Halmahera academic year 2016/2017. Techniques of collecting data by using tests, observations, questionnaires and interviews. Data were analyzed by descriptive analysis and statistical test of t comparison and regression effect test. The results showed that the model of project based learning with scaffolding was effective on mathematical communication ability. Mathematical communication skills and the curiosity character of upper and middle group students are categorized as good and in the high category, while the lower group is considered poor and still in low category. This study aims to: (1) test the effectiveness of Project Based Learning model with scaffolding in improving mathematical communication skills, and (2) to describe mathematical communication skills and students' curiosity through the Project Based Learning model with scaffolding. This research uses approach of mix method of sequential explanatory type. The subject of the research are the students of VIIA class of State Junior High School 18 North Halmahera academic year 2016/2017. Technique of collecting data by using tests, observations, questionnaires and interviews. Data were analyze by descriptive analysis and statistical test of t comparison and regression effect test. The results showed that the model of Project Based Learning with scaffolding was effective on mathematical communication ability. Mathematical communication skills and the curiosity character of upper and middle group students are categorized as good and in the high category, while the lower group is considered poor and still in low category.